Tumour surface regularity predicts survival and benefit from gross total resection in IDH-wildtype glioblastoma patients - Peng Lin; Jin-Shu Pang; Ya-Dan Lin; Qiong Qin; Jia-Yi Lv; Gui-Qian Zhou; Tian-Ming Tan; Wei-Jia Mo; Gang Chen (Insights into Imaging)
Abstract Objectives To evaluate the ability of sphericity in glioblastomas (GBMs) for predicting overall survival (OS) and the survival benefit from gross tumour resection (GTR). Methods Preoperative MRI scans were retrospectively analysed in IDH-wildtype GBM patients from two datasets. After MRI preprocessing and tumour segmentation, tumour sphericity was calculated based on the tumour core region. The prognostic value of tumour surface regularity was evaluated via Kaplan–Meier (K-M) plots, univariate and multivariate Cox proportional hazards analyses. In different surface regularity subgroups, the OS benefit from GTR was evaluated via K-M plots and the restricted mean survival time (RMST). Results This study included 367 patients (median age, 62.0 years [IQR, 54.5–70.5 years]) in the discovery cohort and 475 patients (median age, 63.6 years [IQR, 56.2–71.3 years]) in the validation cohort. Sphericity was an independent predictor of OS in the discovery (p = 0.022, hazard ratio (HR) = 1.45, 95% confidence interval (CI) 1.06–1.99) and validation groups (p = 0.007, HR = 1.38, 95% CI: 1.09–1.74) according to multivariate analysis. Age, extent of resection, and surface regularity composed a prognostic model that separated patients into subgroups with distinct prognoses. Patients in the surface-irregular subgroup benefited from GTR, but patients in the surface-regular subgroup did not in the discovery (p < 0.001 vs. p = 0.056) and validation datasets (p < 0.001 vs. p = 0.11). Conclusions The high surface regularity of IDH-wildtype GBM is significantly correlated with better OS and does not benefit substantially from GTR. Critical relevance statement The proposed imaging marker has the potential to increase the survival prediction efficacy for IDH-wildtype glioblastomas (GBMs), offering a valuable indicator for clinical decision-making. Key Points Sphericity is an independent prognostic factor in IDH-wildtype glioblastomas (GBMs). High sphericity in IDH-wildtype GBM is significantly correlated with better survival. GBM patients with low sphericity could receive survival benefits from gross tumour resection. Graphical Abstract